2021
DOI: 10.3389/fmats.2021.668835
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supported Smart Bacterial Nanocellulose–Phosphotungstic Acid Nanocomposites for Photochromic Applications

Abstract: Bacterial nanocellulose (BNC) is a natural biopolymer obtained by gram-negative bacteria by means of a green and inexhaustible biotechnological process using glucose as producing source. BCN hydrogels is formed by cellulose nanofibrils that maintain an open network structure, an ideal matrix to produce new class of organic-inorganic nanocomposites (OIN) for multifunctional applications. The polyoxometalates (POMs) are complex molecules with several metallic ions sharing oxide ions, forming a highly symmetrical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Among the known POM-based photochromic hybrids, the common organic ligands such as alkylammonium, multicarboxylic acid and sulfonium cations have been widely studied, and exhibit highly tunable photochromic properties with strong color changes. 38–58 However, the color change in these systems is due to photoreduction of Mo/W 6+ ions through electron transfer inside the POM moiety under UV light, and the organic counter ion only acts as a stabilizer of the reduced POM. 59–62 In recent years, with the in-depth study of viologen-based photochromic compounds, 63–77 researchers have found that electron-deficient viologen ligands are capable of hybridizing with electron-rich POMs; this can not only form hybrid materials with diverse structures, but also bring more outstanding redox properties, photoactivity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Among the known POM-based photochromic hybrids, the common organic ligands such as alkylammonium, multicarboxylic acid and sulfonium cations have been widely studied, and exhibit highly tunable photochromic properties with strong color changes. 38–58 However, the color change in these systems is due to photoreduction of Mo/W 6+ ions through electron transfer inside the POM moiety under UV light, and the organic counter ion only acts as a stabilizer of the reduced POM. 59–62 In recent years, with the in-depth study of viologen-based photochromic compounds, 63–77 researchers have found that electron-deficient viologen ligands are capable of hybridizing with electron-rich POMs; this can not only form hybrid materials with diverse structures, but also bring more outstanding redox properties, photoactivity and thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…After incorporation of AMPS to the BC (Fig. 5B), good compatibility and miscibility between BC and AMPS polymers were exhibited on the surface, indicating that the AMPS was uniformly dispersed and embedded in the BC membrane which is supposed to improve its structure to be effectively used in the bioethanol/broth separation process [48,49]. Additionally, the cross-sections of the dried BC membranes in Fig.…”
Section: Sem Analysismentioning
confidence: 92%
“…[16,17] In particular, the flexibility, mechanical durability, high porosity, biocompatibility, [18,19] unique 3D porous nanonetwork, and abundant hydroxyl groups are conducive to the permeation and modification of functional materials, making it an ideal substrate for green manufacturing of photochromic smart textiles. [20][21][22] The initial research on preparing photochromic bacterial cellulose (PBC) was conducted by Hu et al [23] and Santos et al [24] ≈10 years ago. Despite extensive exploration of photochromic textiles, modifications based on fermentation products present several critical challenges.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] and Santos et al. [ 24 ] ≈10 years ago. Despite extensive exploration of photochromic textiles, modifications based on fermentation products present several critical challenges.…”
Section: Introductionmentioning
confidence: 99%